Assessing climate change vulnerability and its effects on food security: Testing a new toolkit in Tanzania - Ulrichs, Martina; Cannon, Terry; Etten, Jacob van; Morimoto, Yasu; Yumbya, John; Kongola, Eliud; Said, Soma; Gevel, Jeske M.J, van de; Newsham, Andrew; Marshall, Mipsie; Kabululu, Sospeter; Kiambi, Dan; et al. (2015)
The working paper presents a new toolkit for the implementation of a participatory vulnerability assessment (PVA) in rural localities, by introducing the methodology, as well as the findings, from a pilot study in Sokoine (Zepisa, Hombolo Ward) in Tanzania. It is based on a participatory methodological approach and follows a multidimensional conceptualisation of social vulnerability to climate change. The methodology is designed to equip project implementers who have limited resources to assess the occurrence and consequences of climate impacts on local livelihood strategies and food systems. It will assist them in understanding local views on how climate change may affect them, what kind of coping strategies are already in place and how their adaptive capacity can be enhanced through measures that are tailored to the profiles of different local groups.